2018
DOI: 10.1016/j.earscirev.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Jurassic paleogeography of the Tian Shan: An evolution driven by far-field tectonics and climate

Abstract: The strongly intracontinental Tian Shan region, in Central Asia represents a key area to understand the long term evolution of continents in general and Asia in particular. If its Paleozoic and Cenozoic geodynamics are well understood, its Mesozoic evolution remains poorly constrained. In order to decipher the paleogeographic and large-scale tectonic evolution of the Tian Shan area during the Jurassic, we compiled, detailed field analyses of sedimentary rocks acquired within and around the Chinese Tian Shan re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 135 publications
(419 reference statements)
2
42
0
Order By: Relevance
“…In spite of alteration by the subsequent Early Cenozoic tectonic deformation, field observation Ritts & Biffi, 2000Edward R. Sobel et al, 2001) and subsurface data (including the seismic reflections and isopach map) clearly show that the Early to Middle Jurassic strata are largely distributed along the Paleozoic inherited faults, especially the ATF shearing zone (Figures 1 and 6). Similar stratigraphic distribution of Early to Middle Jurassic series can also be observed along the Talas Fergana Fault (Morin et al, 2018;Sobel, 1999), in the Kazakh and Turan platform (Thomas et al, 1999), in the pre-Caspian Basin further to the west (Moseley & Tsimmer, 2000) and even in the Hexi Corridor, northeast of the Tibetan Plateau (S. Chen et al, 2014). Following the model proposed by Morin et al (2018), we propose that, in the absence of major collisional event during Early to Middle Jurassic period, the Early to Middle Jurassic strike-slip motion along the ATF and the associated regional extension may have responded to far-field effects of subduction processes along the southern edges of Eurasia.…”
Section: Potential Mechanism Driving the Early Jurassic Intracontinensupporting
confidence: 71%
See 1 more Smart Citation
“…In spite of alteration by the subsequent Early Cenozoic tectonic deformation, field observation Ritts & Biffi, 2000Edward R. Sobel et al, 2001) and subsurface data (including the seismic reflections and isopach map) clearly show that the Early to Middle Jurassic strata are largely distributed along the Paleozoic inherited faults, especially the ATF shearing zone (Figures 1 and 6). Similar stratigraphic distribution of Early to Middle Jurassic series can also be observed along the Talas Fergana Fault (Morin et al, 2018;Sobel, 1999), in the Kazakh and Turan platform (Thomas et al, 1999), in the pre-Caspian Basin further to the west (Moseley & Tsimmer, 2000) and even in the Hexi Corridor, northeast of the Tibetan Plateau (S. Chen et al, 2014). Following the model proposed by Morin et al (2018), we propose that, in the absence of major collisional event during Early to Middle Jurassic period, the Early to Middle Jurassic strike-slip motion along the ATF and the associated regional extension may have responded to far-field effects of subduction processes along the southern edges of Eurasia.…”
Section: Potential Mechanism Driving the Early Jurassic Intracontinensupporting
confidence: 71%
“…Similar stratigraphic distribution of Early to Middle Jurassic series can also be observed along the Talas Fergana Fault (Morin et al, 2018;Sobel, 1999), in the Kazakh and Turan platform (Thomas et al, 1999), in the pre-Caspian Basin further to the west (Moseley & Tsimmer, 2000) and even in the Hexi Corridor, northeast of the Tibetan Plateau (S. Chen et al, 2014). Following the model proposed by Morin et al (2018), we propose that, in the absence of major collisional event during Early to Middle Jurassic period, the Early to Middle Jurassic strike-slip motion along the ATF and the associated regional extension may have responded to far-field effects of subduction processes along the southern edges of Eurasia. The associated stress-field reactivated the major tectonic structures inherited from the Paleozoic (Figure 10).…”
Section: Potential Mechanism Driving the Early Jurassic Intracontinensupporting
confidence: 71%
“…Following the Late Triassic -Early Jurassic tectonic activity, the Jurassic marks the onset of a progressive lowering of the Tian Shan relief indicated by the genesis of a regional scale erosional surface. This flattening of the topography is also well characterized by sedimentological studies which identified a transition from Upper Triassic -Lower Jurassic coarse-grained sediments associated with braided fluvial environments to Middle Jurassic organic-rich meandering-fluvial and lacustrine deposits in both the Junggar and Tarim basins (Hendrix et al, 1992;Eberth et al, 2001;Yang et al, 2015;De Pelsmaeker et al, 2018;Morin et al, 2018). The widespread occurrence of Middle Jurassic coal layers associated to fine -grained sediments throughout the Tian Shan region confirms that most of the relief was already flattened by Middle Jurassic time under rather humid conditions.…”
Section: Ages and Long-term Evolution Of The Planation Surfacesmentioning
confidence: 69%
“…The geological history of this mountain belt was first marked by multiple Paleozoic orogenies (e.g. Windley et al, 1990;Allen et al, 1993;Gao et al, 1998;Gao et al, 2009;Charvet et al, 2011;Xiao et al, 2013;Alexeiev et al, 2015) subsequently followed by a complex Mesozoic evolution characterized by short-lived, low magnitude compressive to strike-slip deformations localized along major structures (Hendrix et al, 1992(Hendrix et al, , 2000Dumitru et al, 2001;Jolivet et al, 2013;Yang et al, 2015;Morin et al, 2018). Finally, a major reactivation of the Tian Shan Range occurred during the Cenozoic in response to the India-Asia collision (e.g.…”
Section: Geological Settingsmentioning
confidence: 99%
See 1 more Smart Citation